Notes on the lecture “The Concept of Time” by Martin Heidegger - Kirchner, Renato (Sofia, 2024)
With the lecture The Concept of Time as its main reference, the purpose of this article is to detail the context in which it was given. In addition, the aim is to highlight the extent to which the reflection proposed by Heidegger on that occasion moves conceptually in a very specific and peculiar perspective. Finally, the aim is also to point out the relationships that the text of the 1924 conference has with other texts by the philosopher from Messkirch and, in this case, both the years before and the years after, as is unequivocally the case with the treatise Being and Time, published in 1927.